EFFECT OF VERMICOMPOST DOSES ON CANABIS SATIVA PHOTOSYNTHESIS-RELATED PARAMETERS, GROWTH AND YIELD (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Hemp, Cannabis sativa is certainly a multifunctional as well as a niche crop, due to great potential for innovative use of its different products. Aspects of hemp mineral nutrition are very important in the cultivation of these plants, in particular to make cultivation environmentally friendly by replacing synthetic fertilizers with organic ones. Among organic fertilizers, vermicompost has gained particular attention within the last decades. Explaining the role of vermicompost, this study evaluated the effects of different doses of this fertilizer on hemps in two separate field studies. In a small-scale field experiment, the effect of two doses of vermicompost and adequate concentrations of mineral elements fertilizers the growth, physiological condition, as well as yield of hemp was compared. The effect of increasing doses of vermicompost on the physiological condition and yield of hemp was analysed in a broader field experiment. The experiments were performed at the Viļāni Scientific Centre of the Agricultural Resources and Economics, in 2017 and 2018, using the Latvian hemp cultivar ‘Pūriņi’. For the experiments, certified vermicompost produced by ‘Eko Zeme’ (Latvia) was used, which was produced from composted cow manure by adding grass biomass. In field experiment, the positive effect of vermicompost on hemp growth was greater than the effect of equivalent mineral fertilizer concentrations. When using vermicompost in increasing doses, better hemp growth (40–60 %) was observed at 5 and 10 t ha-1, stem yield increased on average by 40 % due vermicompost, seed yield ranging from 1.00 t ha-1 in control plants, to 1.56 t ha-1 in 20 t ha-1 in plants treated with 20 t ha–1 vermicompost plants. The weight of 1000 seeds per plant in all variants (from 13.54 to 13.85 g) was relatively close to the indicated maximum level (14.59 g). A statistically significant increase in chlorophyll concentration in plant leaves was observed under the influence of vermicompost. The increase in the Performance Index of the chlorophyll a fluorescence measurement was only for plants in individual experimental variants; regardless of how significant the increase in stem and seed yield was due to the respective doses of vermicompost. In general, the results characterize the growth of hemp in local agroclimatic conditions and allow to expect a stable increase in yield under the influence of vermicompost.